Effect Of Different Drying Methods On Proximate Of Vitamin And Minerals Composition Of Scotch Bonnet (At-Taruhu) (Journal of Food and Dietetics Research, 2026)
Capsicum chinenseis a hot variety of Chili pepper, it is a perennial flowering plant of the Solanaceae family. It is locally  known as atarodo by the Yorubas, osendu by the Igbos and attaruhu by the Hausas of Nigeria. The fruits of C. chinense varies greatly in both color and shape, some appears red, yellow and orange are the most widespread matured colors,  but very few also appear brown and purple. This study was aimed to determine effect of different drying methods on  scotch bonnet. Proximate compositions of the samples were determined using standard methods. The samples have  the following proximate composition; sample A has higher amount of carbohydrate (22.517± 0.7696)%, followed by  moisture (8.9567± 0.1401)% then fiber (19.0767±0.6683)%, then protein (20.66± 1.4072)%, then fat (19.98± 1.3469)%  and the least was ash (8.1300± 0.026). Sample B also contains higher amount of carbohydrate (21.890± 0.4246)%, followed by moisture (11.8400± 0.3576)% then fiber (19.0567±0.5705)%, then protein (18.05± 0.62583)%, then fat (17.71±  0.5116)% and the least was ash (11.09± 1.0076%) and Sample C also contains higher amount of carbohydrate (21.330±  0.3700)%, followed by moisture (17.2333± 0.4751)% then fiber (18.5767±0.4937)%, then protein (17.370± 0.3310)%,  then fat (17.52± 0.4454)% and the least was ash (7.960± 0.9406%).The order of concentration of vitamins in the pepper  content was in this order: Vitamin C > Vitamin A > Vitamin E > Vitamin B2 > Vitamin B1 > Vitamin B3. Scotch Bonnet  had the highest calcium and magnesium contents, oven drying had the highest phosphorus, potassium and iron contents  while sun drying had the highest zinc and sodium contents respectively. The study concluded that shade drying methods  are more suitable than the other ones.
Keywords: Scotch bonnet; proximate; shade drying; perennial plant; chili